Influence of rheological parameters on lava flow morphology inferred from numerical modelling - Zeinalova, Natalya; Bilotta, Giuseppe; Ismail-Zadeh, Alik; Cappello, Annalisa; Ganci, Gaetana; Schilling, Frank (International journal of earth sciences : Geologische Rundschau, 2025)
The dynamics and morphology of lava flows are influenced by lava viscosity. However, the rheological parameters used in lava flow modelling are often subject to considerable uncertainties. To address this, we analyse the influence of key rheological parameters on the advancement and morphology of lava flows using GPUFLOW, a two-dimensional cellular automaton model that simulates Bingham fluid flow on the flanks of Mt. Etna. Our results demonstrate that variations in the initial volume fraction of crystals, the volume fraction of crystals in the equilibrium state, the characteristic time of crystal content growth (i.e. the relaxation time), the melt viscosity, and yield strength significantly impact lava flow patterns. An increased volume fraction of crystals – either at the time of eruption or in the equilibrium state – is associated with reduced advancement of the lava flow. This reduction is attributed to increased viscosity, which promotes vertical thickening of the lava flow and limits its lateral extent. In contrast, when relaxation times exceed the lava flow runout times, the crystal content evolves slowly, allowing the lava flow to advance further with a viscosity close to that of the crystal-free melt viscosity. Lower melt viscosity enhances lava flow mobility, whereas higher melt viscosity encourages shorter and thicker flows. Additionally, the slope of the volcano flank, yield strength, and melt viscosity influence the lava critical thickness, thereby exerting control over the extent of lava advance. These findings provide improved insights into the rheological controls on lava flow dynamics and have important implications for flow hazard assessment and forecasting of lava flows. Graphical Abstract